A New Mode of Excitation Control to Improve Transient Stability: Bang-Bang Insertion of Capacitance in the Field Circuit - Rao V.P.; Rao V.S.S. (My University, 2025)
This letter investigated a new approach to the optimal control of transients in a simple nonlinear power system by contralling excitation with bang-bang insertion of capacitance in the field circuit. The advantages and practical considerations are discussed, and computational results are presented for a specific case. Copyright © 1976 by The Institute of Electrical and Electronics Engineers, Inc.